Answer:
a) The implied differential equation is ![\frac{dN}{725 - N} = kdt](https://tex.z-dn.net/?f=%5Cfrac%7BdN%7D%7B725%20-%20N%7D%20%3D%20kdt)
b) The general equation is ![N = 725 - C e^{-kt}](https://tex.z-dn.net/?f=N%20%3D%20725%20-%20C%20e%5E%7B-kt%7D)
c) The particular equation is ![N = 725 - 325 e^{-0.49t}](https://tex.z-dn.net/?f=N%20%3D%20725%20-%20325%20e%5E%7B-0.49t%7D)
d) The population when t = 5, N(5) = 697 = 700( to the nearest 50)
Step-by-step explanation:
The rate of change of N(t) can be written as dN/dt
According to the question, ![\frac{dN}{dt} \alpha (725 - N(t))](https://tex.z-dn.net/?f=%5Cfrac%7BdN%7D%7Bdt%7D%20%5Calpha%20%28725%20-%20N%28t%29%29)
![\frac{dN}{dt} = k (725 - N)\\\frac{dN}{725 - N} = kdt](https://tex.z-dn.net/?f=%5Cfrac%7BdN%7D%7Bdt%7D%20%3D%20k%20%28725%20-%20N%29%5C%5C%5Cfrac%7BdN%7D%7B725%20-%20N%7D%20%3D%20kdt)
Integrating both sides of the equation
![\int {\frac{1 }{725 - N}} \, dN = \int {k} \, dt\\- ln (725 - N) = kt + C\\ ln (725 - N) = -(kt + C)\\725 - N = e^{-(kt + C)} \\725 - N = e^{-kt} * e^{-C} \\725 - N = C e^{-kt}\\N = 725 - C e^{-kt}](https://tex.z-dn.net/?f=%5Cint%20%7B%5Cfrac%7B1%20%7D%7B725%20-%20N%7D%7D%20%5C%2C%20dN%20%20%3D%20%5Cint%20%7Bk%7D%20%5C%2C%20dt%5C%5C-%20ln%20%28725%20-%20N%29%20%3D%20kt%20%2B%20C%5C%5C%20ln%20%28725%20-%20N%29%20%3D%20-%28kt%20%2B%20C%29%5C%5C725%20-%20N%20%3D%20e%5E%7B-%28kt%20%2B%20C%29%7D%20%5C%5C725%20-%20N%20%3D%20e%5E%7B-kt%7D%20%2A%20e%5E%7B-C%7D%20%5C%5C725%20-%20N%20%3D%20C%20e%5E%7B-kt%7D%5C%5CN%20%3D%20725%20-%20C%20e%5E%7B-kt%7D)
When t = 0, N = 400
![400 = 725 - C e^{-k*0}\\400 = 725 - C\\C = 725 - 400\\C = 325](https://tex.z-dn.net/?f=400%20%3D%20725%20-%20C%20e%5E%7B-k%2A0%7D%5C%5C400%20%3D%20725%20-%20C%5C%5CC%20%3D%20725%20-%20400%5C%5CC%20%3D%20325)
When t = 3, N = 650
![650 = 725 - (325 * e^{-3k})\\325 * e^{-3k} = 75\\e^{-3k} = 75/325\\e^{-3k} = 0.23\\-3k = ln 0.23\\-3k = -1.47\\k = 1.47/3\\k = 0.49](https://tex.z-dn.net/?f=650%20%3D%20725%20-%20%28325%20%2A%20e%5E%7B-3k%7D%29%5C%5C325%20%2A%20e%5E%7B-3k%7D%20%3D%2075%5C%5Ce%5E%7B-3k%7D%20%3D%2075%2F325%5C%5Ce%5E%7B-3k%7D%20%3D%200.23%5C%5C-3k%20%3D%20ln%200.23%5C%5C-3k%20%3D%20-1.47%5C%5Ck%20%3D%201.47%2F3%5C%5Ck%20%3D%200.49)
The equation for the population becomes:
![N = 725 - 325 e^{-0.49t}](https://tex.z-dn.net/?f=N%20%3D%20725%20-%20325%20e%5E%7B-0.49t%7D)
At t = 5, the population becomes:
![N = 725 - 325 e^{-0.49*5}\\N = 725 - 325 e^{-2.45}\\N = 696.95\\N(5) = 697](https://tex.z-dn.net/?f=N%20%3D%20725%20-%20325%20e%5E%7B-0.49%2A5%7D%5C%5CN%20%3D%20725%20-%20325%20e%5E%7B-2.45%7D%5C%5CN%20%3D%20696.95%5C%5CN%285%29%20%3D%20697)
N(5) = 700 ( to the nearest 50)
Answer:
(1, 1), (2, 2.333) and (3, 3.666).
Step-by-step explanation:
So, for x = 1, we have:
4*1 - 3y = 1
3y = 3
y = 1
For x = 2, we have:
4*2 - 3y = 1
3y = 7
y = 2.333
For x = 3, we have:
4*3 - 3y = 1
3y = 11
y = 3.666
The points we need to plot is (1, 1), (2, 2.333) and (3, 3.666).
Answer:
200 feet per minute
Step-by-step explanation:
1000 / 5 gives us the feet per minute
200 feet per minute
Answer: 200 feet per minute
Answer:
x = 24
Step-by-step explanation:
Pythagorean Theorem: a² + b² = c²
<em>a</em> = a leg
<em>b</em> = another leg
<em>c</em> = hypotenuse
Step 1: Plug in known variables
x² + 10² = 26²
Step 2: Evaluate
x² + 100 = 676
Step 3: Isolate <em>x </em>term
x² = 576
Step 4: Isolate <em>x</em>
√x² = √576
x = 24
Problem # 1
Not Factored: (5x^2 - 13x - 6)
Factored: (5x + 2 )(x - 3)
There is no real "work" to be shown for this, you can see that
1) Seperating 5x^2 into 5x and x will get you the equation in the form:
(5x ) (x ) = 5x^2 +
2) To complete this factor you need to guess which two numbers will add together to give you - 13x and multiply to form -6 (from the original unfactored equation). The numbers that will do this are 2 and 3
3) You can plug in negative or positives of those numbers to make sure they give you the exact results you need.
For example testing -2 and 3 you will get: (5x - 2) (x + 3 ) = 5(x^2) - 2x + 15x - 6 = 5x^2 +13x - 6. This is NOT the same as the unfactored equation. So you know -2 and 3 is the wrong choice. Choosing 2 and -3 will give you the answer instead.
As i said, there's no actual "work" to show this, you have to make guesses and try to factor it.
-------------------------------------------------------------------------------------------------
Problem # 2
Not Factored: 4x^4 - 28x^3 + 48x^2
Factored: 4x^2 (x^2 - 7x + 12) =
4x^2 (x - 3) (x - 4)
To solve this, you factor out the 4x^2 from the entire equation. Then you can further factor the quadratic equation by seperating x^2 into (x )(x ) and guessing for which numbers will add to -7x and multiply to 12